Composite high-weather-resistance rubber waterstop and preparation process thereof

Through the design of multi-layer composite structure and dynamic covalent bond chemical structure, combined with the use of nanomaterials and carbon fibers, the problems of aging and insufficient mechanical strength of rubber water stops in harsh environments are solved, and efficient self-repair and production are achieved The process significantly improves the overall performance of the material.

CN119489597APending Publication Date: 2025-02-21HEBEI BAOLI ENG EQUIP GRP CO LTD

Patent Information

Application Number
CN202411565465.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing rubber water stops are prone to aging when exposed to harsh environments for a long time, lack mechanical strength, lack of self-repair ability and low production process efficiency.

Method used

Using a multi-layer composite structure design, including the outer layer consisting of nanotitanium dioxide and nano zinc oxide and rubber matrix, the intermediate layer consisting of ethylene propylene rubber and carbon fiber materials, and the inner layer adopts a dynamic covalent bond chemical structure, and the inner layer is a rubber material with a dynamic covalent bond chemical structure, and Optimized vulcanization process and microwave vulcanization technology are prepared.

Benefits of technology

The comprehensive performance of rubber water stops is significantly improved, including weather resistance, mechanical strength, self-repair capability and production process efficiency, extending service life and reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489597A_ABST
    Figure CN119489597A_ABST
Patent Text Reader

Abstract

The invention relates to the field of waterproof sealing materials, and discloses a composite high-weather-resistance rubber waterstop which is composed of an outer layer, a middle layer and an inner layer. The outer layer contains 3%-8% of nano titanium dioxide, 2%-5% of nano zinc oxide, 50%-70% of a rubber matrix and 1%-3% of an ultraviolet light absorber, and the total proportion of the outer layer is 10%-20%. The middle layer is composed of 70%-85% of EPDM, 5%-10% of carbon fiber and 5%-10% of plasticizer, and the total proportion of the middle layer is 60%-75%. The inner layer is a dynamic covalent bond rubber material and contains 5%-10% of a vulcanizing agent and 1%-3% of an antioxidant, the rubber material accounts for 80%-90%, and the inner layer accounts for 15%-25% in total. Through a multi-layer composite structure, a dynamic covalent bond self-repairing material and an optimized vulcanization process, the comprehensive performance of the water-stop belt is remarkably improved, and particularly the durability and the service life of the water-stop belt in a long-term exposure environment are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof sealing materials, in particular to a composite highly weather-resistant rubber waterstop and a preparation process thereof. Background Art

[0002] Rubber waterstop is a commonly used waterproof and sealing material in civil engineering, tunnel engineering, underground construction and other fields. It is mainly used to prevent water from penetrating into the joints or moving interfaces of concrete structures. As an important sealing component, rubber waterstop plays a key role in preventing water erosion and preventing water seepage from structural cracks. However, with the increasing complexity of construction projects and environmental requirements, the existing rubber waterstop materials and designs have gradually exposed a series of problems and cannot fully meet the increasingly demanding application requirements.

[0003] Existing rubber waterstops are usually made of a single rubber material, such as natural rubber, chloroprene rubber (CR), ethylene propylene diene monomer (EPDM), etc. These materials have certain elasticity, tensile strength and sealing properties, and can meet the basic waterproofing requirements in conventional construction scenarios. However, with the increasing requirements for waterproofing performance, durability and structural stability in projects, the existing rubber waterstop technology faces the following challenges: Insufficient weather resistance Existing rubber waterstops are prone to aging, cracking, and performance degradation when exposed to harsh environments (such as strong ultraviolet rays, ozone, acid rain, and temperature fluctuations) for a long time. Although materials such as EPDM have good heat resistance and weather resistance, their single-layer structure design has limited resistance to ultraviolet rays and ozone. Especially in long-term outdoor exposure, the surface of the waterstop material is prone to aging, causing the material to harden and lose elasticity, thereby affecting the sealing performance. Existing anti-UV and anti-aging solutions usually slow down the aging process by adding antioxidants or UV absorbers, but the effect is not long-lasting, especially under long-term use, there is still the problem of rapid aging.

[0004] Mechanical strength and structural design have limitations Most existing rubber waterstops adopt a single solid structure design, such as rectangular, flat, etc. Although this design is simple, in actual application, with the settlement, thermal expansion and contraction of the engineering structure and the impact of external forces, stress concentration will occur in some local locations of the rubber material, leading to fatigue damage. The single solid structure cannot effectively disperse external forces, and stress concentration can easily lead to fracture and failure of the rubber material. Especially in construction environments with complex forces such as tunnels and bridges, the long-term durability of the waterstop is difficult to guarantee. In addition, the existing design is difficult to cope with the displacement and settlement of buildings under complex working conditions, and the waterstop is prone to failure in such environments.

[0005] Lack of self-repair capability and high maintenance cost In actual applications, rubber waterstops are usually difficult to self-repair after being damaged by external forces or cracked during long-term use, resulting in a decrease in its sealing performance. Once the rubber materials in the prior art are damaged, they often need to be replaced or repaired, which not only increases the construction difficulty and maintenance costs, but also affects the waterproof effect and overall safety of the project. Especially in places where regular maintenance is difficult (such as tunnels and underground projects), the self-repair ability of waterstops is particularly important, but traditional materials do not have this function.

[0006] Inefficient production process and uneven vulcanization The existing production process of rubber waterstop mainly relies on the traditional hot vulcanization process. This process has problems such as long vulcanization time, high energy consumption, and low production efficiency. More importantly, the traditional vulcanization process is prone to uneven vulcanization in thick rubber products, resulting in reduced mechanical properties and waterproof properties of the material. In addition, the existing vulcanization process is difficult to process multi-layer composite materials at the same time, resulting in inconsistent vulcanization degrees of the inner and outer layers, affecting the overall performance stability of the waterstop.

[0007] Therefore, the present invention proposes a composite highly weather-resistant rubber waterstop and a preparation process thereof to solve the deficiencies of the prior art. Summary of the invention

[0008] In view of the problems of existing rubber waterstops in terms of insufficient weather resistance, insufficient mechanical strength, lack of self-repairing ability, and low production process efficiency, the present invention proposes a composite highly weather-resistant rubber waterstop and its preparation process. Through a multi-layer composite structure, dynamic covalent bond self-repairing materials and an optimized vulcanization process, the comprehensive performance of the waterstop is significantly improved, especially the durability and service life in a long-term exposure environment.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions: a composite highly weather-resistant rubber waterstop, the waterstop comprising: The outer layer is composed of nano titanium dioxide, nano zinc oxide and a rubber matrix, wherein the mass of the rubber matrix accounts for 50%-70%, the mass of nano titanium dioxide accounts for 3%-8%, the mass of nano zinc oxide accounts for 2%-5%, and the mass of the ultraviolet absorber accounts for 1%-3%. The outer layer accounts for 10%-20% of the total mass of the waterstop; The middle layer is composed of ethylene propylene diene monomer rubber (EPDM) and carbon fiber material, the mass of EPDM rubber accounts for 70%-85%, the mass of carbon fiber material accounts for 5%-10%, and contains 5%-10% of plasticizer, and the middle layer accounts for 60%-75% of the total mass of the water stop; The inner layer is composed of a rubber material with a dynamic covalent bond chemical structure, the rubber material accounts for 80%-90%, and contains 5%-10% of a vulcanizer and 1%-3% of an antioxidant. The inner layer accounts for 15%-25% of the total mass of the waterstop.

[0010] Preferably, the inner layer is formed by a dynamic vulcanization process, the vulcanization process is carried out at a temperature of 160-180°C, the amount of vulcanizing agent used is 2%-4%, the vulcanization time is 5-10 minutes, and the dynamic covalent bond chemical structure formed during the vulcanization process enables the inner layer material to have a molecular cross-linked structure.

[0011] Preferably, the waterstop has a plurality of cavity structures arranged along its cross-sectional direction, the shape of the cavity is trapezoidal, U-shaped or Ω-shaped, and the wall thickness and height of each cavity are determined by calculation to meet the requirement of uniform stress distribution when subjected to force, and the wall thickness of the cavity is between 1.5-3 mm.

[0012] Preferably, the wall thickness of the cavity gradually decreases from the bottom to the top of the cavity, and the wall thickness ranges from 1.5 to 3 mm.

[0013] Preferably, an expansion material is provided in the cavity, and the expansion material is a water-absorbing resin or bentonite. The mass of the expansion material accounts for 3%-7% of the total mass of the waterstop, and the volume increases by 30% to 50% after encountering water.

[0014] Preferably, the preparation process of the composite high weather-resistant rubber waterstop comprises the following steps: (1) Ingredients: 60%-75% of EPDM rubber, 3%-5% of nano titanium dioxide, 2%-3% of nano zinc oxide, 5%-8% of carbon fiber, 5%-10% of bio-based plasticizer, 2%-4% of vulcanizer, and 1%-2% of antioxidant are mixed according to the above proportions and preliminarily kneaded at a temperature of 120 to 150° C.; (2) Ultrasonic dispersion: The preliminarily mixed rubber matrix is ​​placed in an ultrasonic device for treatment, with an ultrasonic frequency of 20 to 40 kHz and a dispersion time of 15 to 30 minutes; (3) Dynamic vulcanization: The mixed rubber material after ultrasonic treatment is heated to 160 to 180°C for 5 to 10 minutes to complete the dynamic vulcanization process; (4) Extrusion molding: The dynamically vulcanized rubber material is processed into the required multi-cavity rubber waterstop structure through an extrusion molding process.

[0015] Preferably, the vulcanization process adopts microwave vulcanization technology, the microwave power is set at 800 to 1200 watts, and the vulcanization time is 2 to 5 minutes to ensure uniform vulcanization.

[0016] Preferably, the bio-based plasticizer is a soybean oil-based plasticizer or a glycerol-based plasticizer, and its mass accounts for 10% to 20% of the total weight of the mixture.

[0017] Preferably, the vulcanizing agent is dicumyl peroxide, the antioxidant is a diphenylamine antioxidant, and the amounts of the vulcanizing agent and the antioxidant are 2%-4% and 1%-2%, respectively.

[0018] The present invention provides a composite highly weather-resistant rubber waterstop and a preparation process thereof, which has the following beneficial effects: 1. The present invention effectively combines the advantages of different materials by adopting a multi-layer composite structure design of an outer layer, an intermediate layer and an inner layer. The outer layer is composed of nano-titanium dioxide, nano-zinc oxide and a rubber matrix, which not only gives the material excellent UV resistance and aging resistance, but also improves its corrosion resistance and environmental adaptability. The middle layer uses ethylene propylene diene monomer rubber (EPDM) combined with carbon fiber material to enhance the tensile strength and tear resistance of the waterstop, and further improves its toughness and flexibility through plasticizers. Compared with the technical solution of using a single rubber material in the prior art, the present invention significantly improves the comprehensive weather resistance and mechanical properties of the waterstop, solves the problem of easy aging and rapid strength decay of the existing rubber waterstop under long-term outdoor exposure, and extends the service life of the waterstop.

[0019] 2. The inner layer of the present invention adopts a dynamic covalent bond chemical structure and forms a highly cross-linked rubber material through a dynamic vulcanization process. The material has the property of being able to heal spontaneously through molecular chain reorganization and cross-linking reaction after being partially damaged. In practical applications, when slight cracks or damage appear in the inner layer material of the waterstop, the dynamic covalent bond structure can undergo molecular reorganization at room temperature or low temperature to restore its original mechanical strength and sealing performance. Compared with the technical solutions in the prior art that traditional rubber materials are difficult to repair or need to be replaced after damage, the present invention greatly extends the service life of the waterstop while reducing the frequency of maintenance and replacement, solving the problem of the waterstop being easily damaged and having high maintenance costs in the prior art.

[0020] 3. The present invention adopts a multi-cavity structure design and combines a variety of cross-sectional shapes such as trapezoidal, U-shaped or Ω-shaped to make the waterstop have better stress distribution characteristics when subjected to external force. The design optimizes the wall thickness and height of each cavity through finite element analysis, so that when the waterstop is under stress, the cavity structure can evenly disperse the stress and avoid fatigue damage caused by local stress concentration. In addition, the cavity structure can also enhance the overall flexibility and compression resistance of the waterstop, ensuring that it can still maintain a good sealing effect when the building settles or slightly displaces. Compared with the waterstop with a single solid structure in the prior art, the present invention effectively solves the problem of the waterstop being prone to cracking and failure during long-term use due to stress concentration, and greatly improves its adaptability and stability in complex construction environments.

[0021] 4. The present invention adopts a solution that combines microwave vulcanization technology with a dynamic vulcanization process. During the vulcanization process, microwave heating is used to achieve rapid and uniform temperature distribution, making the vulcanization of the rubber material more accurate and efficient, and ensuring the uniform cross-linking of each layer of material. At the same time, the dynamic vulcanization technology ensures the cross-linking density and chemical stability of the rubber material, forming a rubber composite material with excellent mechanical properties. Compared with the traditional hot vulcanization process commonly used in the prior art, the present invention greatly shortens the vulcanization time, improves production efficiency, and reduces energy consumption. In addition, the application of microwave vulcanization technology effectively avoids the problem of unevenness that may occur during the vulcanization process, making the overall performance of the waterstop more stable and reliable, and solving the technical defects of the traditional vulcanization process that causes unstable product performance due to uneven vulcanization. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart for preparing a composite highly weather-resistant rubber waterstop. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Please refer to the attached Figure 1 : Example

[0025] Ingredients: Mix 60% EPDM, 3% nano titanium dioxide, 2% nano zinc oxide, 6% carbon fiber, 8% bio-based plasticizer, 2.5% vulcanizer, and 1.5% antioxidant. In this formula, EPDM rubber is the base material with good weather resistance and flexibility, nano titanium dioxide and nano zinc oxide provide ultraviolet blocking properties, and carbon fiber enhances tensile properties.

[0026] Initial mixing: Mix in an internal mixer at 120°C for 15 minutes to disperse all materials evenly and mix the rubber matrix evenly.

[0027] Ultrasonic dispersion: The mixed rubber matrix is ​​placed in an ultrasonic device for treatment. The ultrasonic frequency is set to 30 kHz and the dispersion time is 25 minutes to ensure the uniform dispersion of the nanomaterials in the rubber matrix, enhance the dispersion effect of the filler, and improve the weather resistance and mechanical strength of the material.

[0028] Dynamic vulcanization: The rubber matrix is ​​vulcanized at 170°C for 8 minutes using a dynamic vulcanization process to form a cross-linked network with a dynamic covalent bond structure, thereby enhancing the self-healing ability of the material.

[0029] Extrusion molding: The vulcanized rubber material is extruded to form a waterstop with a trapezoidal, U-shaped and Ω-shaped cavity structure.

[0030] Microwave vulcanization: The formed waterstop is further processed using microwave vulcanization technology with a power of 1000 watts and a vulcanization time of 3 minutes to ensure uniform overall vulcanization and improve production efficiency.

[0031] Summary of the embodiment: This embodiment adopts a moderate content of nanomaterials (such as 3% nano titanium dioxide and 2% nano zinc oxide), which ensures that the rubber waterstop has strong UV resistance and anti-aging properties while maintaining good processability. By combining dynamic vulcanization with microwave vulcanization process, the self-healing performance and vulcanization uniformity of the material are significantly improved. Due to the low proportion of nanofillers, the weather resistance and strength of the waterstop in this embodiment are at a medium level, which is suitable for ordinary outdoor projects. Example

[0032] Ingredients: The EPDM is mixed at a mass ratio of 75%, nano titanium dioxide 4%, nano zinc oxide 3%, carbon fiber 5%, bio-based plasticizer 10%, vulcanizer 3%, and antioxidant 2%. The EPDM ratio is relatively high in this formula, which enhances the high temperature resistance and anti-aging ability of the water stop, and at the same time improves the anti-ultraviolet performance by increasing the proportion of nano materials.

[0033] Initial mixing: Mix at 130°C for 20 minutes to make the materials fully and evenly mixed.

[0034] Ultrasonic dispersion: The ultrasonic frequency was set to 25 kHz and the dispersion time was 20 minutes to ensure the uniform distribution of the nanomaterials in the rubber matrix and further enhance the material’s aging and corrosion resistance.

[0035] Dynamic vulcanization: Vulcanization at 160°C for 10 minutes forms a stable cross-linking network, enhancing the mechanical properties and self-healing ability of the rubber material.

[0036] Extrusion molding: The vulcanized rubber material is formed into a waterstop with a trapezoidal and U-shaped cavity structure through extrusion equipment.

[0037] Microwave vulcanization: The vulcanization process was performed using microwave vulcanization technology with a power of 800 watts and a vulcanization time of 2 minutes to ensure uniform vulcanization of the material.

[0038] Summary of the embodiments: The ratio of nano-titanium dioxide and nano-zinc oxide in this embodiment is relatively high, which further improves the UV resistance and weather resistance of the rubber material, while the carbon fiber enhances the tensile strength and toughness of the waterstop. Due to the high vulcanization temperature and long vulcanization time, the mechanical properties of the material are more prominent, and it is especially suitable for projects that are exposed to ultraviolet rays and high temperature environments for a long time. Although the production efficiency is slightly lower than that of Example 1, the durability and crack resistance are significantly improved. Example

[0039] Ingredients: The EPDM rubber (EPDM) is mixed at a mass ratio of 70%, nano titanium dioxide 5%, nano zinc oxide 3%, carbon fiber 8%, bio-based plasticizer 9%, vulcanizer 4%, and antioxidant 1%. The high proportion of carbon fiber and nanomaterials in this formula enhances the mechanical strength and tear resistance of the waterstop.

[0040] Initial mixing: Mix at 140°C for 18 minutes to ensure that the materials are thoroughly mixed.

[0041] Ultrasonic dispersion The ultrasonic frequency was set to 40 kHz and the dispersion time was 15 min to ensure that a higher content of nanomaterials could be evenly dispersed and to avoid performance degradation caused by filler aggregation.

[0042] Dynamic vulcanization Vulcanization at 180°C for 5 minutes forms a highly cross-linked dynamic covalent bond structure, improving the self-healing ability of the material.

[0043] Extrusion molding: The rubber waterstop is extruded with Ω-shaped and trapezoidal cavities. The cavity structure provides good compression resistance and flexibility.

[0044] Microwave vulcanization: Use 1200 watts of microwave vulcanization technology and a vulcanization time of 5 minutes to ensure uniform vulcanization.

[0045] Summary of the Example: This example uses a higher proportion of nanomaterials and carbon fibers, which significantly improves the mechanical strength and tear resistance of the waterstop. Due to the high carbon fiber content, the mixing process is complicated and the ultrasonic treatment time is long, but the final material shows higher fatigue resistance and weather resistance. It is suitable for engineering applications with higher strength requirements.

[0046] Comparative experiment 1: Weather resistance comparison experiment Purpose: The ultraviolet aging test was used to test the weather resistance of Examples 1, 2, and 3 of the present invention and the prior art EPDM rubber waterstop under long-term ultraviolet irradiation.

[0047] Experimental Materials: Composite high weather-resistant rubber waterstop samples prepared in Examples 1, 2 and 3 of the present invention.

[0048] The existing EPDM rubber waterstop sample is made of 100% EPDM.

[0049] Prior art process steps: Ingredients: Use 100% EPDM as the matrix, add 5% plasticizer and 2% vulcanizer and mix well.

[0050] Mixing: Mix the ingredients in an internal mixer at 120°C for 15 minutes.

[0051] Vulcanization: The mixed rubber was vulcanized at 160°C for 10 minutes.

[0052] Molding: The rubber material is molded into a single-layer waterstop through extrusion equipment.

[0053] Experimental steps: Sample preparation: Cut samples of 50 mm×50 mm×2 mm from the waterstop strips of Examples 1, 2, 3 and the prior art, respectively.

[0054] UV aging test: Place the sample in a UV aging test chamber, set the temperature to 60°C, and the UV irradiation intensity to 1W / m², simulating a 500-hour UV irradiation environment.

[0055] Tensile test: Samples were taken every 100 hours and the tensile strength of the samples was measured using a tensile tester according to GB / T 528 standard.

[0056] Surface inspection: Observe the surface cracks under a high-power microscope during each test.

[0057] Experimental results: Sample No. Initial tensile strength (MPa) Tensile strength after 500 hours (MPa) Tensile strength retention rate (%) Surface cracking Example 1 15 13 86 none Example 2 16 14 88 none Example 3 14 12 85 none Prior art 12 7 58 Obvious cracking Data Analysis: Example 2 exhibits the best weather resistance, maintaining 88% of the tensile strength, and its UV resistance comes from the higher ratio of nano-titanium dioxide and nano-zinc oxide (4% and 3%).

[0058] The tensile strength retention rates of Example 1 and Example 3 are 86% and 85% respectively, indicating that both have strong anti-aging capabilities.

[0059] The EPDM samples of the existing technology performed poorly, with the tensile strength retention rate of only 58% after 500 hours of UV aging, and obvious cracks appeared on the surface, indicating its poor weather resistance.

[0060] Comparative experiment 2: Mechanical strength comparison experiment Purpose: The mechanical strength of Examples 1, 2, and 3 of the present invention and the prior art EPDM rubber waterstop were tested, mainly comparing the tensile strength and elongation at break.

[0061] Experimental Materials: Composite high weather-resistant rubber waterstop samples prepared in Examples 1, 2, and 3 of the present invention.

[0062] Prior art EPDM rubber waterstop sample.

[0063] Prior art process steps: Ingredients: 100% EPDM matrix, 5% plasticizer and 3% carbon black.

[0064] Mixing: Mix in an internal mixer at 120°C for 15 minutes.

[0065] Vulcanization: Vulcanize in a vulcanizer at 160°C for 8 minutes.

[0066] Molding: Molded into a solid structural waterstop through extrusion equipment.

[0067] Experimental steps: Sample preparation: Cut 10mm×100mm samples.

[0068] Tensile test: Use a tensile tester to measure the tensile strength and elongation at break according to GB / T 528 standard.

[0069] Calculation of elongation at break: record the elongation length of the sample when it breaks and calculate the elongation at break.

[0070] Experimental results: Sample No. Tensile strength(MPa) Elongation at break (%) Example 1 15 420 Example 2 16 430 Example 3 14 410 Prior art 10 300 Data Analysis: Example 2 exhibits the highest tensile strength and elongation at break, reaching 16 MPa and 430%, which is due to its higher proportion of EPDM and carbon fiber materials, providing better reinforcement effect.

[0071] The tensile strengths of Example 1 and Example 3 are 15 MPa and 14 MPa, respectively, indicating that different ratios of carbon fiber and plasticizer have a certain effect on the strength and flexibility of the material.

[0072] The tensile strength of the EPDM sample of the prior art is only 10 MPa and the elongation at break is 300%, showing poor mechanical properties, mainly due to the lack of reinforcement materials.

[0073] Comparative experiment 3: Self-repair ability comparison experiment Purpose: The self-repairing ability of Examples 1, 2, and 3 of the present invention and the prior art EPDM rubber waterstop was tested.

[0074] Experimental Materials: Composite high weather-resistant rubber waterstop samples prepared in Examples 1, 2, and 3 of the present invention.

[0075] Prior art EPDM rubber waterstop sample.

[0076] Prior art process steps: Produced according to the prior art formula, no self-repairing ability.

[0077] Experimental steps: Scratch test: Use a scratch tester to make a scratch with a width of 2 mm and a length of 50 mm on the surface of each sample.

[0078] Repair observation: The samples were placed at room temperature, and the scratch recovery area was measured after 24 hours, 48 ​​hours, and 72 hours.

[0079] Recovery rate calculation: The repair effect is evaluated by calculating the ratio of the recovered scratch width to the original scratch width.

[0080] Experimental results: Sample No. Initial scratch width (mm) Scratch recovery time (one hour) Recovery rate (%) Example 1 2.0 48 85 Example 2 2.5 48 88 Example 3 2.0 48 83 Prior art 2.0 No recovery 0 Data Analysis: The embodiments of the present invention exhibit significant self-repairing ability, and the recovery rate of Embodiment 2 is the highest, which is 88%, which is related to the higher cross-linking density of the dynamic covalent bond chemical structure.

[0081] The recovery rates of Example 1 and Example 3 are 85% and 83% respectively, which also show good self-repairing performance.

[0082] The EPDM material in the prior art has no self-repairing function and the scratches are not restored, which shows that the dynamic vulcanization process and material selection of the present invention significantly improve the self-repairing ability.

[0083] Comparative experiment 4: Production process efficiency comparison experiment Purpose: The production process efficiency of Examples 1, 2, and 3 of the present invention and the prior art EPDM rubber waterstop was tested, mainly comparing the vulcanization time, energy consumption, and vulcanization uniformity.

[0084] Experimental Materials: Embodiments 1, 2 and 3 of the present invention are composite high-weather-resistant rubber waterstops prepared using microwave vulcanization technology.

[0085] The prior art uses EPDM rubber waterstop prepared by traditional hot vulcanization process.

[0086] Prior art process steps: Ingredients and mixing: Same as above.

[0087] Hot vulcanization: Use a traditional hot vulcanizer, set the vulcanization temperature to 160°C, and the vulcanization time to 15 minutes.

[0088] Experimental steps: Vulcanization time measurement: record the time required for vulcanization of each sample.

[0089] Energy consumption calculation: The power consumption during the vulcanization process is recorded by a power meter.

[0090] Vulcanization uniformity test: Use a tensile tester to test the tensile strength of different parts of the vulcanized sample to check the vulcanization uniformity.

[0091] Experimental results: Sample No. Curing time (minutes) Energy consumption (kWh) Vulcanization uniformity Example 1 8 0.5 excellent Example 2 7 0.45 excellent Example 3 6 0.48 excellent Prior art 15 1.0 generally Data Analysis: The embodiments of the present invention adopt microwave vulcanization technology, and the vulcanization time is significantly shortened. The vulcanization time of Embodiment 3 is the shortest (6 minutes), and the energy consumption is lower than the traditional hot vulcanization process.

[0092] The traditional hot vulcanization process takes 15 minutes to complete and consumes up to 1.0 kWh of energy. The vulcanization is uneven, resulting in differences in tensile strength in different parts.

[0093] The microwave vulcanization technology of the present invention makes the vulcanization more uniform and significantly improves the energy efficiency through the action of electromagnetic waves.

[0094] Summarize: The present invention has excellent performance in weather resistance, mechanical strength, self-repairing ability, production process efficiency, etc., and significantly improves the overall performance of the waterstop through a multi-layer composite structure, dynamic vulcanization and microwave vulcanization processes.

[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite highly weather-resistant rubber waterstop, characterized in that: The water stop comprises: The outer layer is composed of nano titanium dioxide, nano zinc oxide and a rubber matrix, wherein the mass of the rubber matrix accounts for 50%-70%, the mass of nano titanium dioxide accounts for 3%-8%, the mass of nano zinc oxide accounts for 2%-5%, and the mass of the ultraviolet absorber accounts for 1%-3%. The outer layer accounts for 10%-20% of the total mass of the waterstop; The middle layer is composed of EPDM rubber and carbon fiber material, the mass of EPDM rubber accounts for 70%-85%, the mass of carbon fiber material accounts for 5%-10%, and contains 5%-10% of plasticizer, and the middle layer accounts for 60%-75% of the total mass of the waterstop; The inner layer is composed of a rubber material with a dynamic covalent bond chemical structure, the rubber material accounts for 80%-90%, and contains 5%-10% of a vulcanizer and 1%-3% of an antioxidant. The inner layer accounts for 15%-25% of the total mass of the waterstop.

2. A composite highly weather-resistant rubber waterstop according to claim 1, characterized in that: The particle sizes of the nano titanium dioxide and nano zinc oxide in the outer layer are 10-50 nanometers, and the mass ratio of the nano titanium dioxide and nano zinc oxide is 1:1 to 2:

1.

3. A composite highly weather-resistant rubber waterstop and its preparation process according to claim 1, characterized in that: The inner layer is formed by a dynamic vulcanization process, which is carried out at a temperature of 160-180°C, with a vulcanizing agent dosage of 2%-4% and a vulcanization time of 5-10 minutes. The dynamic covalent bond chemical structure formed during the vulcanization process enables the inner layer material to have a molecular cross-linked structure.

4. The composite highly weather-resistant rubber waterstop according to claim 1, characterized in that: The waterstop has multiple cavity structures arranged along its cross-sectional direction. The shape of the cavity is trapezoidal, U-shaped or Ω-shaped, and the wall thickness and height of each cavity are determined by calculation to meet the requirement of uniform stress distribution when subjected to force. The wall thickness of the cavity is between 1.5-3 mm.

5. A composite highly weather-resistant rubber waterstop according to claim 4, characterized in that: The wall thickness of the cavity gradually decreases from the bottom to the top of the cavity, and the wall thickness ranges from 1.5 to 3 mm.

6. A composite highly weather-resistant rubber waterstop according to claim 5, characterized in that: An expansion material is arranged in the cavity. The expansion material is a water-absorbing resin or bentonite. The mass of the expansion material accounts for 3%-7% of the total mass of the waterstop, and the volume increases by 30% to 50% after encountering water.

7. The preparation process of the composite high weather-resistant rubber waterstop according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Ingredients: 60%-75% of EPDM rubber, 3%-5% of nano titanium dioxide, 2%-3% of nano zinc oxide, 5%-8% of carbon fiber, 5%-10% of bio-based plasticizer, 2%-4% of vulcanizer, and 1%-2% of antioxidant are mixed according to the above proportions and preliminarily kneaded at a temperature of 120 to 150° C.; (2) Ultrasonic dispersion: The preliminarily mixed rubber matrix is ​​placed in an ultrasonic device for treatment, with an ultrasonic frequency of 20 to 40 kHz and a dispersion time of 15 to 30 minutes; (3) Dynamic vulcanization: The mixed rubber material after ultrasonic treatment is heated to 160 to 180°C for 5 to 10 minutes to complete the dynamic vulcanization process; (4) Extrusion molding: The dynamically vulcanized rubber material is processed into the required multi-cavity rubber waterstop structure through an extrusion molding process.

8. The process for preparing a composite highly weather-resistant rubber waterstop according to claim 7, characterized in that: The vulcanization process adopts microwave vulcanization technology, the microwave power is set at 800 to 1200 watts, and the vulcanization time is 2 to 5 minutes to ensure uniform vulcanization.

9. The process for preparing a composite highly weather-resistant rubber waterstop according to claim 7, characterized in that: The bio-based plasticizer is a soybean oil-based plasticizer or a glycerol-based plasticizer, and its mass accounts for 10% to 20% of the total weight of the mixture.

10. The process for preparing a composite highly weather-resistant rubber waterstop according to claim 7, characterized in that: The vulcanizing agent is dicumyl peroxide, the antioxidant is a diphenylamine antioxidant, and the dosage of the vulcanizing agent and the antioxidant is 2%-4% and 1%-2% respectively.

Citation Information

Patent Citations

  • Replaceable surface layer combined sealing structure for concrete structural joint

    CN105951680A

  • Natural odor-resistant rubber with high tensile strength and preparation method thereof

    CN113308029A

  • Water-swellable rubber waterstop convenient for construction and preparation method of water-swellable rubber waterstop convenient for construction

    CN118581929A

  • Compounded rubber waterstop

    CN204589922U

Cited By

  • High-adhesiveness composite material for rubber dam and preparation method of high-adhesiveness composite material

    CN120534031A

  • Highly adhesive composite material for rubber dams and method for its production

    CN120534031B

  • An Integrated Rubber Plate For Rubber Dam And Its Manufacturing Method

    KR103000100B1